"Female Voices on Ink": The Sexual Politics of Petitions in Colonial Igboland, 1892–1960. Issue 4 (2nd October 2019) - Alozie, Bright C.
ABSTRACT: While historians have, of course, employed a host of documentary sources in reconstructing the colonial history of Nigeria, few have used petitions to understand the dynamic negotiations that occurred between the colonizer and the colonized. As a result, a vital primary source of history has been underutilized. Likewise, the voices of women lamentably have suffered the same fate as the use of petitions. This study seeks to fill this important gap by examining selected petitions and written correspondence between Igbo women and British officials in the period from 1892 to 1960. Continuously undermined by male-dominated colonial institutions and structures, African women acted in varied and complex manners from subtle to overt opposition, and sometimes violent resistance. One response was through petition-writing as women took to the pen to articulate their concerns. Petitioning became both a disabling and enabling force in exploring the relationship between subjectivity and power relations. How are scholars to understand the interactions between the often-neglected, ordinary female subjects and the British authorities? To what extent did their petitions shift the balance of patriarchal power and give voice to the otherwise "silent" women? Analysis of petitions written by women in colonial Igboland demonstrates how petition-writing gave females a subtle yet powerful voice, or agency, in a rigidly hierarchical colonial political system. This study argues that instead of simply looking at these petitions as another set of documents, they should be regarded as unique sources in which colonial subjects' thoughts and desires are revealed. In addition, these neglected sources should be treated as an integral part of the complex power politics among colonial subjects as well as between them and officials. In thinking through these petitions, this case study reframes the sexual politics of petitions and challenges dominant, institutionalized gender ideologies that have defined women as nearly powerless and passive.